Centralized control system in interdomain routing environments - Mahamah Sebakor (2018)
Currently, most multihomed-to-multiple providers need to control the flow of interdomain traffic for both performance and economical reasons. This is usually done by manual configuration of the Border Gateway Protocol (BGP) on routers to control interdomain traffic. In this paper, we approach the solution to the traffic engineering problem with BGPbased traffic engineering techniques and reservationbased control for priority traffic. We propose a centralized control system placed inside the autonomous systems (AS) which controls the interdomain traffic. The manual control reserves capacity for priority IP traffics on allocated links. The control processes for the remaining IP traffics are performed automatically. The utilization, drop rate, and performances of links are investigated. The simulation results show that the proposed control system is able to avoid possible link congestion, increase utilization, decrease drop rate, and can also reserve capacity of links for priority IP traffics.